Response of soil organic carbon decomposition to intensified water variability co-determined by the microbial community and aggregate changes in a temperate grassland soil of northern China. (January 2023) - Chen, Kangli; Huo, Tianci; Zhang, Yaowen; Guo, Tongtian; Liang, Junyi
Abstract: The effect of precipitation variability on soil organic carbon (SOC) decomposition is vital in regulating the global carbon (C) cycle and climate change. However, the response of SOC decomposition to different magnitudes of precipitation variability and its dependence on moisture level are still controversial. In this study, we conducted a three-month incubation experiment that manipulated soil water levels and the intensity of water variability with a homogenized topsoil from a temperate grassland. Results showed that intensified water variability significantly reduced CO2 emissions at the low-water level, but did not affect the SOC decomposition at the high-water level. Meanwhile, the microbial community was significantly altered by the intensified water variability, showing a decrease in microbial biomass and increases in the fungi: bacterial ratio and Gram-positive: Gram-negative bacteria ratio, which tended to suppress the SOC decomposition. However, the intensified water variability significantly stimulated the breakdown of macro-aggregates to micro-aggregates at the high-water level, which promoted the substrate availability in soil and compensated for the suppressed SOC decomposition by microbial community responses. The findings highlight that the response of SOC decomposition to intensified water variability is co-determined by the microbial community responses and aggregate instabilities. Highlights: Intensified water variability changes the microbial community and suppresses C release. Suppressed C release is compensated by aggregates breakdown at the high-water level. SOC response to water variability seems to be driven by microbial-physical interactions.